Consumo de vancomicina iny. 500 mg en los servicios de medicina interna, cirugia y unidad de cuidados intensivos del hospital regional docente de trujillo 2008” - Guzmán Graos, Maureen Evelyn (2009)
This study had as objective to determinate the consume of vancomycin inj. 500 mg at service of Internal Medicine, Surgery and Intensive Care Unit of the Hospital Regional Docent de Trujillo 2008. It was made a descriptive-retrospective. For the determination of consumption was used the methodology of defined daily doses (DDD). The consumption of Vancomycin Inj. 500 mg in Internal Medicine, Surgery and Intensive Care Unit of Hospital Regional Docent de Trujillo was 1519, 639 and 2099 bottles vials respectively. The average consumption of bottles vials of Vancomycin Inj. 500 mg expressed DDD/100camas/día in Internal Medicine, Surgery and Intensive Care Unit of Hospital Regional Docent de Trujillo was 2.15, 0.81 and 39.83 respectively. The trend of consumption in internal medicine and surgery, showed a decrease and increase respectively of this medication over time, not being statistically significant for presenting a (p> 0.05). The trend in consumption in the service of Intensive Care Unit, shows a decrease of this medication over time were statistically significant for presenting a (p <0.05), and finally the cost of consumption generated vials vials Vancomycin Inj. 500 mg in Internal Medicine, Surgery and Intensive Care Unit of Hospital Regional Docent de Trujillo was S /. 13 397.58, 635.98 and S/.5 S /. 18 513.18 new soles respectively